The Ontology of a Semiotic Experience (Functional-Pragmatic Point of View) - Leszczak, Oleg (Respectus Philologicus, 2004)
The paper focuses on the ontological status of the key subjects in semiotics, namely a sign, a signal and a semiotic activity from the point of functional-pragmatic methodology; such notions as "semantics", "syntactic" and "pragmatics" are submitted to a functional critical review. The sign and the signal are considered as informational two-side units and as the functions of experience differing according to their ontological status as the subjects of experience being appointed by the units as the signal objects introducing them in the course of interpersonal communication. All types of signals (both natural and arbitral ones) are deliberately equated in the ontological relation. Simultaneously, the sign is differentiated ontologically as a mental function of thinking and the signal as a psycho-physiological function. From the point of the functional-pragmatic methodology, the traditional treatment of such notions as semantics, syntactic and pragmatics of a sign is reconsidered. The sign is treated as having dual functional value - pragmatic (teleological) and structural (semantic and formal).
Keywords: semiotics; semiotic activity; sign; signal; functionalism; pragmatism; ontology